Optimization of Public Services by Bhabinkamtibmas in Improving Community Trust Building in the Assisted Village of the Bogor Police - Maharrani Setyadevi Hartanto (Advances in Police Science Research Journal, 2021)
The background of this research is to improve community trust building towards the police by optimizing public services carried out by members of the Bhabinkamtibmas Bogor Police. The public demand for good public services as regulated in Law Number 25 of 2009 concerning Public Services that every organization or agency that deals directly with the community is obliged to provide public services in accordance with its objectives. The Bogor Polres is manifested by the Binmas Unit, especially members of the Bhabinkamtibmas as the spearhead of the National Police. The objectives of the research are (1) to describe the public services of the Bogor Police, (2) to find out the obstacles and obstacles of Bhabinkamtibmas members in optimizing services to the community, (3) to describe the performance in optimizing public services at the Bogor Police. To discuss the problem, the concept of mass communication, police science, the grand strategy of the National Police, and Gibson and Sinta Tri Kumilausari's optimization theory, and Surjadi's theory of public service is used. This research was conducted with a qualitative approach, using two methods, namely survey and descriptive qualitative, as well as data collection techniques by interview, observation, and document study. The results of the study are (1) public services at the Bogor Police are good but not yet optimal, (2) the obstacles and constraints that Bhabinkamtibmas have greatly affect the services provided to the community from timeliness, accuracy in solving problems, and awareness of the community, (3) how Bhabinkamtibmas overcomes obstacles and obstacles. The recommendations of this research are the use of the E-Bhabinkamtibmas application by all Indonesian people, skills training for Bhabinkamtibmas members, and conducting a routine evaluation of Bhabinkamtibmas activities.